2017
DOI: 10.1042/bsr20160611
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into DNA methylation and its critical implications in diabetic vascular complications

Abstract: Recent epidemiological and clinical studies have shown that type 2 diabetic patients can develop diabetic vascular complications even after intensive glycaemic control. It has been suggested that this phenomenon could be explained by the hypothesis of ‘metabolic memory’. The underlying mechanisms between these enduring effects and the prior hyperglycaemic state are still not well understood. Preliminary studies demonstrate that hyperglycaemia can regulate gene expression by epigenetic modifications, such as DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…The elucidation of epigenetic changes involved in microvascular complications could improve our knowledge of pathophysiology and therapeutic management of these diseases, an important public health issue. The role of DNA methylation in vascular complications of diabetes has been recently reviewed [ 34 ]. Several lines of evidence described distinct methylation patterns in diabetes-associated cardiovascular complications [ 35 38 ], suggesting that high glucose-induced oxidative stress is an important mediator [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The elucidation of epigenetic changes involved in microvascular complications could improve our knowledge of pathophysiology and therapeutic management of these diseases, an important public health issue. The role of DNA methylation in vascular complications of diabetes has been recently reviewed [ 34 ]. Several lines of evidence described distinct methylation patterns in diabetes-associated cardiovascular complications [ 35 38 ], suggesting that high glucose-induced oxidative stress is an important mediator [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation in vascular complications of diabetes have been investigated and reviewed in a recent review ( 62 ). El-Osta ( 63 ) reported that short-term exposure of aortic endothelial cells to high glucose-induced promoter DNA methylation of NF-kB p65 subunit, an important mediator of cardiac fibrosis.…”
Section: Dna Methylation In Diabetes-induced Microvascular Complicatimentioning
confidence: 99%
“…There is growing evidence that epigenetic dysregulation is involved in diabetes and its associated DN and DR [ 12 17 ]. In addition, epigenetic alterations and the C677T genotype were associated with risk for chronic renal failure and dialysis in patients with renal insufficiency due to low enzyme activity and global hypomethylation of DNA that alters the expression of different systemic alleles [ 18 ].…”
Section: Introductionmentioning
confidence: 99%